2021
DOI: 10.1001/jamacardio.2021.1825
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coronary Artery Disease and Coronary Microvascular Dysfunction in Patients With Heart Failure With Preserved Ejection Fraction

Abstract: IMPORTANCECoronary artery disease (CAD) and coronary microvascular dysfunction (CMD) may contribute to the pathophysiologic characteristics of heart failure with preserved ejection fraction (HFpEF). However, the prevalence of CAD and CMD have not been systematically studied.OBJECTIVE To examine the prevalence of CAD and CMD in hospitalized patients with HFpEF. DESIGN, SETTING, AND PARTICIPANTSA total of 106 consecutive patients hospitalized with HFpEF were evaluated in this prospective, multicenter, cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 41 publications
8
119
2
1
Order By: Relevance
“…Various researchers have proposed ischaemic HFpEF as a distinct entity. 19 , 20 Shah et al . proposed that abnormalities in coronary microcirculation can support the occurrence of HFpEF in some patients, 21 but there is currently no routine evaluation of microvascular dysfunction in HFpEF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have proposed ischaemic HFpEF as a distinct entity. 19 , 20 Shah et al . proposed that abnormalities in coronary microcirculation can support the occurrence of HFpEF in some patients, 21 but there is currently no routine evaluation of microvascular dysfunction in HFpEF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a high prevalence of coronary microvascular dysfunction in HFpEF patients. 19 Whether abnormal coronary microcirculation occurs in almost all HFpEF patients with evidence of macroscopic CAD deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Their expression is characteristic of decreased eNOS activity and NO bioavailability. This encourages the recruitment and trafficking of circulating leukocytes to the subendothelial, which initiates the formation of atherosclerotic lesions formation and the progression of atherosclerosis which hastens the incidence of HFpEF ( Venugopal et al, 2002 ; Kolluru et al, 2010 ; Westermann et al, 2011 ; Rush et al, 2021 ). These aforementioned CME dysfunctionalities have been associated with E2 deficiency.…”
Section: Physiological and Pathophysiological Interplays Between E2 And Ers And βArs In Cardiac Function Modulationmentioning
confidence: 99%
“…Apart from vascular events, several studies have shown evidence of CMD in patients with heart failure with preserved ejection fraction (HFpEF), such that it might be a key pathophysiologic player [ 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Moreover, in patients without flow-limiting epicardial CAD, impaired CFR was independently associated with diastolic dysfunction and adverse events [ 118 , 119 ].…”
Section: Prognosismentioning
confidence: 99%